Pro-poor growth and governance in South Asia : decentralization and participatory development - Wignaraja,Ponna(Editor) Susil Sirivardana(Editor) (SAGE Publications, 2004)
"This volume breaks new ground by investigating in depth the three important agendas of governance, decentralization/devolution, and poverty eradication, and by highlighting how they can be coordinated to fashion a genuinely pro-poor macro-micro development strategy. It will attract a wide readership among development activists and policy makers while also being of interest to scholars from various academic disciplines including development studies, politics, economics, sociology and public administration."--BOOK JACKET.